Effects of Aerobic, Resistance, and Combined ExercisePrograms on Arthritis Related Symptoms - Scott Jamieson; Katherine DeVivo; Kailyn Horn; Jessica Moxley; Christine Pellegrini (Lesya Ukrainka Volyn National University, 2024)
Physical activity is a therapeutic modality in alleviating arthritis-related symptoms, yet most individuals fail to attain recommended guidelines. The Purpose of the Research was to briefly summarize the effects of aerobic and resistance exercise on arthritis symptoms, highlight some of the challenges of these programs, and provide future strategies to increase participation in physical activity. Research Methods. A brief search of the recent literature on physical activity interventions and health related outcomes in adults with arthritis was performed. Research Results. For aerobic activity, improvements in arthritis outcomes including pain, function, and quality of life are common in supervised sessions a minimum of 3 times per week; however, adherence to participation often remains low. Engaging in resistance exercise at least 12 weeks has been shown to promote improvements in arthritis related symptoms with higher intensity not always leading to greater improvements. Prior evidence has suggested mixed exercise to be the least efficacious compared to single exercise programs. Conclusions. Future research should explore strategies to increase adherence to aerobic and resistance exercise programs, which could lead to greater reductions in pain and improvements in physical function in adults with arthritis. Alternative delivery modalities over the standard in person, supervised sessions should be considered and may be more appropriate to older adults with arthritis. More research is also needed to understand why multicomponent exercise programs appear less effective than programs focusing only on one activity behavior. Finally, engaging stakeholders in the development and implementation of exercise programs may help to ensure these programs are acceptable for adults with arthritis.